Images of a lipid bilayer at molecular resolution by scanning tunneling microscopy. - Smith, D P (1987)
The molecular structure of a fatty acid bilayer has been recorded with a scanning tunneling microscope operating in air. The molecular film, a bilayer of cadmium icosanoate (arachidate), was deposited onto a graphite substrate by the Langmuir-Blodgett technique. The packing of the lipid film was found to be partially ordered. Along one axis of the triclinic unit cell the intermolecular distance varied randomly around a mean of 5.84 A with a SD of 0.24 A. Along the other axis the mean distance was 4.1 A and appeared to vary monotonically over several intermolecular distances, indicating that a superstructure of longer range may exist. The molecular density was one molecular per 19.4 A2. The surprising ability of the scanning tunneling microscope to image the individual molecular chains demonstrates that electrons from the graphite can be transferred along the molecular chains for a distance of 50 A.